„Barsuki" by L. Leonov and literature of the early twenties - Kondiurina, E. (Literatūra, 1974)
The comparison of the novel "Barsuki" with the literature of the early twenties makes it possible to bring out the writer's creative individuality. The importance and originality of the novel are conditioned by the very realities depicted in "Barsuki".
Keywords: -